Training on herbal plants and simplicia processing at the Miftahul Jannah Mosque, Malang Regency - Ratna Djuniwati Lisminingsih (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Most people have knowledge of herbal medicine, but understanding of Thibbun Nabawi, especially herbal and simplicia needs to be improved among the congregation of the Miftahul Jannah Mosque in Malang. Thibbun Nabawi is one of the alternatives regarding disease recognition, hygiene, prevention, and treatment based on the Al Qur’an and Al Hadith. Training activities have been carried out aimed at improving the knowledge, attitudes, and skills of mosque congregations as well as expanding the function of the mosque in addition to being a place of worship as well as to improve the health and welfare of the community. The method of implementing the activities carried out by developing the community includes team formation, goal formulation, user identification, gathering and analyzing needs, determining problem solution priorities, preparation, implementation, mentoring, review and evaluation, as well as determining new target needs. The profile of the training participants aged 20-60 years is 78.9% with the highest level of education equivalent to a diploma at 42.1%. There was an increase in knowledge test scores by 57.9%, attitudes by 2.63%, and skills by 92.11% after training on the introduction of herbal plants and making simplicia. Participants were 100% satisfied with the training held at the Miftahul Jannah Mosque and the mosque has widely functioned to improve the health and welfare of the community.